APPLICATION OF PICTURE MEDIA TO IMPROVE STUDENTS' ENGLISH PRESENT CONTINUOUS TENSE SPEAKING ABILITY - Milati, Ni Made (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
The ability to speak English with good and correct pronunciation, accuracy, fluency, and intonation is a challenge for students in forming new knowledge. There are still many students who do not master speaking skills in English. Therefore, this study aims to evaluate the application of image media techniques to students' speaking skills in the present continuous tense. This research is descriptive qualitative research. This research was carried out in three cycles, each consisting of two learning cycles or face-to-face. The research subjects were 30 education participants. The method used to collect data is observation, interviews, and tests. The instrument used to collect data is a test question. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that students in cycles I, II, and III had an average score which indicated that image media techniques could improve English speaking skills in the present continuous tense. It was concluded that the application of image media could effectively improve the ability to speak English. Picture media can facilitate students in learning English. This finding can also be used as a reference for teachers to improve the speaking learning process.